2021
DOI: 10.1080/21507740.2021.1958100
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Neuromodulation and Self-Perception in Clinical Treatment of Refractory Epilepsy

Abstract: Background: Newer "closed-loop" neurostimulation devices in development could, in theory, induce changes to patients' personalities and self-perceptions. Empirically, however, only limited data of patient and family experiences exist. Responsive neurostimulation (RNS) as a treatment for refractory epilepsy is the first approved and commercially available closed-loop brain stimulation system in clinical practice, presenting an opportunity to observe how conceptual neuroethical concerns manifest in clinical trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The measure is an extension of the standard CDR and includes two additional domains that are predominantly affected in FTD: behavior and language. Each patient’s CDR plus NACC FTLD global score was calculated based on the scoring rules by Miyagawa and colleagues ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure is an extension of the standard CDR and includes two additional domains that are predominantly affected in FTD: behavior and language. Each patient’s CDR plus NACC FTLD global score was calculated based on the scoring rules by Miyagawa and colleagues ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five investigators coded the data independently and subsequently compared and discussed the codes until a consensus was reached. Lastly, divergences in theme categorization were discussed until a consensus was established ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, a typical electrical stimulation protocol is applied in open-loop mode to deliver consistent pre-programmed stimulation to the target organs or physiological systems irrespective of their dynamic states. In contrast, closed-loop systems continuously monitor brain or physiological activity, decode relevant neural signals in real time, and modulate such activities by stimulation when certain physiological states or conditions are met ( Haeusermann et al, 2021 ). The stimulation parameters can also be adjusted dynamically in real time to acquire desired state-specific effects while minimizing the undesired side effects, therefore the closed-loop mode is thought to be more dynamic and efficient than the open-loop systems ( Haeusermann et al, 2021 , Zanos, 2019 ).…”
Section: Neuromodulation-induced Neuroplasticitymentioning
confidence: 99%
“…In contrast, closed-loop systems continuously monitor brain or physiological activity, decode relevant neural signals in real time, and modulate such activities by stimulation when certain physiological states or conditions are met ( Haeusermann et al, 2021 ). The stimulation parameters can also be adjusted dynamically in real time to acquire desired state-specific effects while minimizing the undesired side effects, therefore the closed-loop mode is thought to be more dynamic and efficient than the open-loop systems ( Haeusermann et al, 2021 , Zanos, 2019 ). The closed-loop neuromodulation systems have been used experimentally to facilitate the activity-dependent adaptive neuroplasticity leading to sensorimotor function restoration after SCI, and might have sustained therapeutic benefits in chronic applications ( Jackson and Zimmermann, 2012 , Zanos, 2019 ).…”
Section: Neuromodulation-induced Neuroplasticitymentioning
confidence: 99%
“…This non-optimal approach is inferior to so-called closed-loop techniques, which automatically adapt to the patients current brain/health state. Such an adaptive, or closed-loop, approach has been introduced for intracranial (Hartshorn and Jobst, 2018 ; Prosky et al, 2021 ; Stanslaski et al, 2022 ) and transcranial stimulation (Tervo et al, 2022 ) and has been shown to improve neurostimulation in major depression patients (Scangos et al, 2021 ), epilepsy (Haeusermann et al, 2023 ) and affective and anxiety disorders (Guerrero Moreno et al, 2021 ). These proposed closed-loop methods are adaptive in the sense that a pre-defined stimulation signal is applied when observed brain activity fulfills certain criteria, such as passing an amplitude or power threshold.…”
Section: Introductionmentioning
confidence: 99%